Genetic effects and potential parents in cowpea - Dias,Francisco Tiago Cunha (2016)
ABSTRACT Six cowpea genotypes and their F2 hybrid combinations were evaluated for general and specific combining ability. The Griffing's diallel cross design, Method 2, and mixed model B were used. The genotypes and hybrids differed statistically (p <0.01) for the 10 studied traits. With regard to the general and specific combining ability, there were statistical differences at 1% probability for all traits. The presence of additive and non-additive gene effects paves the way for breeding new hybrid cultivars. However, additive gene effects were predominant in the trait expression. Genotypes CE-542, CE-954 and CE-796 were identified as the most promising of the test group for inclusion in cowpea breeding programs.